Non-perturbative thermal flows and resummations - Litim, Daniel F.; Pawlowski, Jan M. (Journal of high energy physics, 2006)
We construct a functional renormalisation group for thermal fluctuations. Thermal resummations are naturally built in, and the infrared problem of thermal fluctuations is well under control. The viability of the approach is exemplified for thermal scalar field theories. In gauge theories the present setting allows for the construction of a gauge-invariant thermal renormalisation group.
Gesehen am 06.12.2017